Is There a Cranial Nerve Other Than the 7th Co-Involved in Bell’s Palsy? Answer to the Systematic Review - Razif A; Aspalilah A; Mohd Amir K; Wong KH; Siti Nurma Hanim H; Choy KW; Nor Farid MN; Muhammad Hibatullah R (Med & Health, 2024)
Med & Health Jun 2022; 17(1): 44-61